Correlation of TG/HDL Ratio and LDL/HDL Ratio with The Incidence of Coronary Artery Disease (CAD) at General Hospital of Buleleng Regency - Gupta Arya Gumilang P; Susila IK; Kiki Wulandari P; Raka Mahasadu IGA (The International Journal of Medical Science and Health Research, 2025)
Background: CAD is a leading cause of death in both industrialised and developing nations, primarily affecting the younger generation. Triglycerides (TG) to high-density lipoprotein (HDL) cholesterol ratios (TG/HDL) and low-density lipoprotein (LDL) to HDL ratios (LDL/HDL) have been linked to cardiovascular disease. Objective: The objective of this research is to ascertain the relationship between the incidence of CAD and the TG/HDL and LDL/HDL ratios. Method: Analytical observational study with a cross-sectional approach conducted on 210 CAD patients at General Hospital of Buleleng Regency in 2024-2025. Data analysis was performed using the SPSS. Determination of the cut-off value was carried out using the Receiver Operating Characteristic (ROC) curve, then followed by chi-square analysis and logistic regression. Results: Average age of the sample was 60.53 ± 12.647 years and the majority were <65 years old (67.6%). Based on the ROC curve, the cut-off value for the TG/HDL ratio was 2.84 (AUC= 0.45; 95%CI (0.302-0.508); p<0.07) and LDL/HDL ratio was 2.38 (AUC= 0.503; 95%CI (0.398-0.608); p<0.96). Based on the chi-square test, there was no significant relationship between the TG/HDL ratio (OR=1.71; 95%CI=0.92-3.17; p=0.08) or the LDL/HDL ratio (OR=0.94; 95%CI=0.52-1.70; p=0.85) with the incidence of CAD. Based on multivariate analysis, a significant relationship was obtained between a high TG/HDL ratio and the incidence of CAD (AOR=0.42; 95%CI=1.88-0.979; p=0.04). Conclusion: There is a significant relationship between a high TG/HDL ratio and the incidence of CAD.